Aplikasi analisis pinch untuk menurunkan konsumsi steam di bagian process house pabrik gula - Daniyanto Daniyanto; Fathurrahman Rifai (Jurnal Rekayasa Proses, 2013)
The energy efficiency of sugar factory can be indicated by variable steam on cane (SOC). SOC is defined as weight of steam consumption per weight of crushed cane. The smaller the SOC, the energy efficiency of sugar mills is better. The main source of fuel in sugar mill is bagasse. The sugar factory will be efficient if SOC is less than 50%. If SOC value is more than 50%, it will cause additional fuel other than bagasse. If SOC is less than 40%, the cane sugar mill can do cogeneration and produce electricity for sale. This study aims to reduce SOC by reducing steam consumption in the process house through configuration process innovation with pinch analysis.The results showed that pinch analysis could be used to reduce steam consumption in sugar mill. Utilization of steam from evaporator could reduce steam consumption in the process house. The change in process configuration could provide SOC decrease by 8.8% from its former state. Steam produced by evaporator 2 could be used as heat source for heater 1 and heater 2, meanwhile steam produced by evaporator 1 as a heat source for vacuum pan. Exhaust steam could be used only for heater 3 and vacuum pan.